2016
DOI: 10.1007/s10549-016-3934-5
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of androgen receptor expression in invasive breast cancer: transcriptomic and protein expression analysis

Abstract: Background: Differential prognostic roles of Androgen Receptor (AR) have been proposed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
83
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 53 publications
10
83
1
1
Order By: Relevance
“…AR was prognostic in this study for all breast cancer cases in both cohorts, which likely reflects its negative correlation with tumor size and proliferative capacity, regardless of ERa status as shown in this study and previously reported (3,5,55). A recent meta-analysis in which AR mRNA expression was correlated with various gene signatures in large combined breast cancer cohorts strongly supports this concept (26).…”
Section: Discussionsupporting
confidence: 83%
“…AR was prognostic in this study for all breast cancer cases in both cohorts, which likely reflects its negative correlation with tumor size and proliferative capacity, regardless of ERa status as shown in this study and previously reported (3,5,55). A recent meta-analysis in which AR mRNA expression was correlated with various gene signatures in large combined breast cancer cohorts strongly supports this concept (26).…”
Section: Discussionsupporting
confidence: 83%
“…Our data were further supported by Jiang et al [15]. who showed that AR expression was associated with decreased DFS in TNBC, but were not in agreement with a recent study, which indicated that AR expression was associated with favorable prognosis such as smaller tumor size, lower grade, and overall survival, particularly in the luminal breast cancer subtypes [30]. Nevertheless, emerging evidence implied intratumoral heterogeneity as a considerable issue that might influence the suitability of core biopsy.…”
Section: Discussionsupporting
confidence: 65%
“…However, although showing a trend toward improvement, the difference in OS was not statistically significant [61]. Aleskandarany et al performed a retrospective cohort study of stage I-III patients ( n = 1141) with tumors ≤5 cm from 1987 to 1997 [62]. High AR expression was associated with longer breast cancer specific survival (BCSS) and was an independent predictor of better outcome regardless of tumor size, grade and nodal stage.…”
Section: Prognostic Implications Of Ar In Er+ Breast Cancermentioning
confidence: 99%